Treatment of primary central nervous system lymphomas - I. V. Cherkashina; M. A. Vernyuk; A. M. Chervontseva; E. E. Gushchina; L. S. Khayrullina; V. V. Lunin; P. A. Zeynalova; A. A. Fedenko (Онкогематология)
Primary lymphoma of the central nervous system (PLCNS) is a rare form of extranodal lymphoma characterized by an aggressive course. In recent decades, the treatment of this disease has undergone significant changes. Modern treatment of PLCNS consists of two steps – induction and consolidation of remission. Improved overall survival of PLCNS patients was achieved through the use of combined immunochemotherapy regimens with high doses of methotrexate and/or cytarabine, which are currently the standard of induction therapy. High-dose chemotherapy followed by autologous hematopoietic stem cell transplantation at the consolidation stage provides the most complete elimination of the residual tumor clone. The most effective modes of conditioning are those with the inclusion of tiotepa. In elderly and comorbid patients who are not candidates for autologous hematopoietic stem cell transplantation, promising results were obtained while using maintenance therapy with procarbazine or temozolomide, and further researches will allow us to study the effectiveness of monocolonal anti-CD20 antibodies – rituximab and obinutuzumab.Treatment options for patients with relapses and / or refractory forms of PLCNS are limited. Certain successes were obtained with the use of new drugs – ibrutinib, nivolumab, lenalidomide, obinutuzumab.